x + y = 7/2
4x - 3y = -14
From the first equation, x = 7/2 - y
Sub this in the second equation:
4( 7/2 - y) - 3y = -14
14 - 4y - 3y = -14
28 = 7y ...........................y = 4
Put this back in the first equation to find x:
x = (7/2 - 4) = -1/2
Check your work in the second equation:
4(-1/2) - 3(4) = -14
(-2) - (12) = -14..................Good!
2007-01-10 05:53:07
·
answer #1
·
answered by MamaMia © 7
·
1⤊
0⤋
x + y = 7/2- - - - - -Equation 1
4x - 3y = - 14- - - - -Equation 2
- - - - - - - - -
Substitute Method equation 1
x + y = 7/2
x + y - x = 3.5 - x
y = 3.5 - x
The answer is y = 3.5 -- x
Insert the y value into equation 2
- - - - - - - - - -
4x - 3y = - 14
4x - 3(3.5 - x) = - 14
4x - 10.5 + 3x = - 14
7x - 10.5 + 10.5 = - 14 + 10.5
7x = - 3.5
7x/7 = - 3.5/7
x = - 0.5
The answer is x = - 0.5
Insert the x value into equation 2
- - - - - - - - - - - - - - - - - - - - - -
4x - 3y = - 14
4(- 0.5) - 3y = - 14
- 2 - 3y = - 14
- 2 - 3y + 2 = - 14 + 2
- 3y = - 12
- 3y /-3 = - 12 / - 3
y = 4
The answer is y = 4
Insert the y value into equation 2
- - - - - - - - - - - - - - - - - - - - - -
Check for equation 2
4x - 3y = - 14
4(-0.5) - 3(4) = - 14
- 2 - 12 = - 14
- 14 = - 14
- - - - - - -
Check for equation 1
x + y = 7/2
- 0.5 + 4 = 3.5
3.5 = 3.5
- - - - - - - - -
The solution set is { - 0.5, 4 }
- - - - - - - - s-
2007-01-10 06:13:27
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
The key to this is that you can't solve an equation with two unknowns, can you? So you have to get it down to one unknown.
Pick either they x or the y. Solve for it. Then plug in the answer for it into your variable in the other equation.
Example: x+ y = 1 and 2x + y = 5.
I'll solve the fist eq for x. x=1-y.
So now, in the other eq, I subsitute 1-y wherever I see x.
So in the second eq, I now have 2(1-y) + y =5.
Now I can solve for y! After that I can use one of the original eq's and the value I just got for y to solve for x.
Just apply that method to your equations!!! Good luck!
2007-01-10 05:54:02
·
answer #3
·
answered by aperson 3
·
1⤊
0⤋
x+y = 7/2
x = 7/2-y
4x-3y = -14
4(7/2-y)-3y = -14
14-4y-3y = -14
-7y = -14-14
-7y = -28
7y = 28
y = 28/7
y = 4
x = 7/2-y
x = 7/2-4
x = 7/2-8/2
x = -1/2
2007-01-10 06:18:24
·
answer #4
·
answered by Nicole 3
·
0⤊
0⤋
x = -1/2
y = 4
2007-01-10 05:51:41
·
answer #5
·
answered by e_kueh 2
·
1⤊
0⤋
y=7/2-x
4x-3(7/2-x)=-14
4x-21/2+3x=-14
7x=21/2-14
x=-3.5/7
x=-1/2
y=7/2-x
y=7/2+1/2
y=4
2007-01-10 06:01:26
·
answer #6
·
answered by Nipi 2
·
0⤊
0⤋